Restriction site-associated DNA sequencing - Wang, Xiaoping; Sun, Minshan; Xiong, Yuanyuan; Liu, Xiao; Li, Chunhua; Wang, Yun; Tang, Xiaobo (PloS one, 2024)
Worldwide, tea is a popular beverage; within the realm of Chinese tea, Sichuan tea holds particular significance for its role in the origin and composition of Chinese tea cultivars. Sichuan tea is noted for its rich content of free amino acids (FAAs) and tea polyphenols (TPs), which has made it an important subject for studying genetic diversity and the genes regulating these compounds. In this study, 139 varieties of tea were collected from areas in Sichuan Province, China, with similar geographical and climatic conditions. The FAA content was approximately 3% and the TP content was approximately 17%. Using RAD sequencing, 5,656,224 variant loci were identified, primarily comprising SNPs (94.17%) and indels (5.83%). Evolutionary analysis revealed that genetic divergence was not closely linked to the collection location. Population structure analysis confirmed a division into two main populations having a similar composition to the phylogenetic clusters. Screening for FAA-related SNPs identified significant loci associated with 33 genes that potentially regulate FAA content. Similarly, TP-related analysis pinpointed 8 SNPs significantly linked to 20 candidate genes. Notably, genetic associations hinted at the genes involved in the stress response and the accumulation of phenolic compounds, enhancing the understanding of determinants of tea quality. This research underscores the potential for molecular breeding based on genetic insights, suggesting pathways to improve the FAA and TP contents in tea. These findings not only provide a solid foundation for exploring gene-chemical interactions but also offer practical strategies for improving the nutritional and sensory attributes of tea cultivars through informed breeding practices.